IMPLEMENTASI PEMASARAN 7P SEBAGAI STRATEGI KEPALA SEKOLAH DALAM MENINGKATKAN DAYA SAING SMP ISLAM Al AZHAR 57 JAMBI - Aisya, Afrawita; MY, Mahmud; Fitriani, Suci (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the principal's strategy in marketing SMP Islam Al Azhar 57 Jambi through the implementation of the 7P marketing mix (Product, Price, Place, Promotion, People, Process, Physical Evidence). The primary issue addressed is the school's less strategic location far from the city center, which nevertheless managed to significantly increase student enrollment from 10 students (2022) to 30 students (2024). The methodology employed is a qualitative descriptive approach with data collection techniques including in-depth interviews, observation, and documentation. The results indicate that the principal successfully overcame geographical barriers through systematic strategies. In the product aspect, the school relies on flagship programs such as Tahsin Tamyiz and academic achievements. The price strategy involves adjusting rates to the local market and digitalizing payments. Although the location is on the outskirts, it is converted into an advantage of a quiet and conducive learning environment. Promotion is carried out extensively through social media (Instagram, TikTok, Facebook, YouTube) and interactive events like "Albifest." The people aspect emphasizes the role of teachers as school ambassadors, while the process is managed through bi-weekly evaluations and strategic collaborations (MoU) with institutions such as UIN and UNJA. Finally, physical evidence in the form of building facilities meeting Al Azhar's national standards serves as a key visual attraction. Overall, the integrated implementation of the 7P marketing mix has successfully built a positive brand image and public trust while enhancing the institution's competitiveness.